TEACHING A FOREIGN LANGUAGE IN THE 21ST CENTURY - Alimova, Marina (Журнал иностранных языков и лингвистики, 2021)
This article deals with the use of information technologies, such as Internet resources, which help to implement a personality-oriented approach to learning, provide individualization and differentiation of learning, taking into account the abilities of students, their level of training, aptitudes, etc. The Internet forms the ability and skills of foreign colloquial speech, teaches foreign vocabulary and grammar, providing genuine interest and, consequently, efficiency. A teacher working in a modern school needs to use not only basic, but also auxiliary teaching tools to achieve the goals of teaching a foreign language. Keywords